Experimental Investigation of Compressive and Flexural Strength of Lime-Surkhi Mortar - Bharati, Prashant; Khatakho, Rajwala; Byanju, Rojan; Suwal, Salina; Prajapati, Ratna Shova (International Journal on Engineering Technology, 2026)
Lime-surkhi mortar is a traditional binder used in historic masonry structures in Nepal. Despite its widespread application, compressive and flexural properties of lime-surkhi mortar remain poorly quantified, limiting its reliable use in heritage conservation and structural assessment. This study experimentally investigates the compressive and flexural behavior of lime-surkhi mortar prepared with quicklime-based lime putty, varying surkhi and sand proportions at a constant lime content. Following initial screening of thirteen mix ratios, the 1:1:2 and 1:2:2 mixes were selected for detailed analysis. Specimens were air-cured at 70–80% relative humidity and tested at 7 and 28 days. Cube compressive strength increased by approximately 22 times for the 1:1:2 mix and 14 times for the 1:2:2 mix between 7 and 28 days. Masonry prism compressive strength increased by about 1.7 times for both mixes. While the 1:2:2 mix showed higher cube compressive strength, the 1:1:2 mix exhibited superior prism performance, highlighting the significance of mortar–unit interaction. The flexural strength of the 1:1:2 mix increased slightly with curing, whereas the 1:2:2 mix showed a decline at 28 days. These findings provide empirical data for selecting lime-surkhi mortars in heritage repair and low-load masonry applications.